2021
DOI: 10.1039/d0tc05649a
|View full text |Cite
|
Sign up to set email alerts
|

Predicted septuple-atomic-layer Janus MSiGeN4 (M = Mo and W) monolayers with Rashba spin splitting and high electron carrier mobilities

Abstract: In this work, Janus monolayers are predicted for a new 2D MA2Z4 family by means of first-principles calculations. The predicted MSiGeN4 (M = Mo and W) monolayers exhibit dynamic, thermodynamic and mechanical stability, and they are indirect band-gap semiconductors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 59 publications
2
111
0
Order By: Relevance
“…The values of the C 2D and E d are obtained by tting the strain-dependent energy and band-edge position. 32,33 The strain-dependent energy change and band edge positions of all three Janus structures GaInX 3 are shown in Fig. 7.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…The values of the C 2D and E d are obtained by tting the strain-dependent energy and band-edge position. 32,33 The strain-dependent energy change and band edge positions of all three Janus structures GaInX 3 are shown in Fig. 7.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…The calculated C 2D is 71.68 Nm −1 , which are very smaller than ones of monolayer MSi 2 N 4 (M=Ti, Zr, Hf, Cr, Mo and W) and Janus MSiGeN 4 (M=Mo and W) 15,49 , indicating that monolayer SrAlGaSe 4 is not rigid. The Poisson's ratio ν is also calculated by C 12 /C 11 , and it is 0.37.…”
Section: Crystal Structure and Stabilitymentioning
confidence: 81%
“…Firstly, the C 11 and C 12 are calculated with GGA by SSR, and they are 54.14 Nm −1 and 23.30 Nm −1 , which are smaller than ones of unstrained SrAlGaSe 4 monolayer. Tensile strain reduced C 11 and C 12 have been found in many 2D materials 49,55 . And then, we use the orthorhombic supercell as the computational cell (in…”
Section: Piezoelectric Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…29 This made MoSiN the focus of intensive research aiming to uncover its novel properties. [30][31][32][33][34][35][36][37][38][39] Following the successful MoSiN preparation, many MX 2 Y 4 (M = Cr, V, Mo, W, Ta; X = Si, Ge; and Y = N, As, P) monolayers have been studied. 40,41 It was found that WSi 2 N 4 , CrSi 2 N 4 , and MoSi 2 N 4 monolayers have the highest piezoelectric coefficients as compared with the other known 2D materials.…”
mentioning
confidence: 99%